Existence of Periodic Solutions to Multidelay Functional Differential Equations of Second Order - Cemil Tunç; Ramazan Yazgan (Abstract and Applied Analysis)
Using Lyapunov-Krasovskii functional approach, we establish a new result to guarantee the existence of periodic solutions of a certain multidelay nonlinear functional differential equation of second order. By this work, we extend and improve some earlier result in the literature.